Impact of Beta‐Amyloid Biomarkers on Performance of Digital Mind Mapping Tasks in Alzheimer's Disease Patients. - Chang, Chan; Lee, Soo Jung; Na, Duk L.; Yoon, Ji Hye (International Journal of Language & Communication Disorders (John Wiley & Sons, Inc.))
Background: Alzheimer's disease (AD) patients experience cognitive decline due to the deposition of beta‐amyloid, which particularly affects their ability to retrieve words in language tasks. A mind map is an activity that involves freely associating and retrieving words related to a given category, providing an integrated assessment of cognitive and linguistic abilities. Objective: This study aimed to identify the various characteristics observed during the performance of a digital mind map task in patients with AD pathology, with beta‐amyloid deposition confirmed by positron emission tomography imaging. Methods: The study involved 48 adults aged 50 and over (30 patients with AD pathology and 18 healthy controls, HC). Participants completed a mind map task where they generated and retrieved words related to specific keywords (travel, family and food). Performance was analysed and compared across three main aspects: (1) keyword responses (number of blanks filled, number of words written), (2) performance time (preparation time for retrieval, writing time, total task time), and (3) word diversity (number of unique words, number of repeated words). Results: First, in terms of keyword responses, there was no significant difference between groups in the number of blanks filled; however, the AD pathology group wrote fewer words than HC. Error analysis revealed that the AD patients were more likely to provide elaborations and non‐words compared to HC. Second, regarding performance time, the AD pathology group took longer to prepare for word retrieval and to write the words. Third, in terms of word diversity, the AD pathology group generated fewer unique words and tended to repeat words more often than HC. Conclusions: The study confirms that patients with AD pathology experience difficulties in using their mental lexicon to activate and select appropriate words for retrieval due to damage in the temporal‐parietal regions caused by beta‐amyloid deposition. This study highlights the potential of digital mind maps as a novel word retrieval task for early differentiation of cognitive impairment in AD. WHAT THIS PAPER ADDS: What is already known on the subjectAlzheimer's disease (AD) is a progressive neurodegenerative disorder marked by beta‐amyloid(Aβ) plaques and tau tangles, leading to neuronal loss in memory‐related regions. Aβ disrupts neural connectivity, especially in the temporal and parietal lobes, impairing memory and language. Traditional language tasks, such as naming and verbal fluency, are used to detect early cognitive changes but often fail to reliably distinguish mild cognitive impairment from early AD due to pathological diversity. Mind mapping, which requires associative word retrieval and integrates executive, semantic, and lexical processes, may provide a more comprehensive assessment, but its diagnostic value in AD pathology group not yet well studied.What this paper adds to the existing knowledgeThis study is the first to apply a digital mind mapping task to patients with AD pathology who have objectively confirmed Aβ deposition, directly linking pathological biomarkers to cognitive‐linguistic performance. The findings demonstrate that patients with AD pathology, compared to healthy controls, exhibit significant deficits in mind mapping: they write fewer words, produce more circumlocutory and non‐word responses, require longer preparation and writing times, and generate less diverse vocabulary. By employing a digital platform, the study provides objective, quantitative measurements of word retrieval, response time, and word diversity, offering a novel approach to assessing the multifaceted cognitive‐linguistic deficits associated with AD pathology.What are the potential or actual clinical implications of this work?The digital mind mapping task offers a sensitive and ecologically valid tool for detecting early cognitive‐linguistic impairment in AD, especially in patients with confirmed Aβ pathology. The multifactorial assessment of word retrieval, timing, and diversity may enhance early differentiation of AD from normal aging and other cognitive disorders, supporting earlier intervention and more precise monitoring of disease progression. Integrating digital mind mapping into clinical practice could improve the identification of subtle language deficits not captured by traditional tasks, contributing to more comprehensive cognitive screening and tailored therapeutic strategies for individuals at risk of or with AD.